The Role Played by Compassion International in the Improvement of Children's Welfare : a case study of Mukono district - Adongo, Charity (Kampala : Uganda Christian University, 2009)
Discriptive Cataloging Uganda Christian University. BCDM
includes bibliographical references and appendices.
Keywords: Children welfare